"It’s a mystery!": A case study of implementing forensic science into preschool as scientific inquiry - Howitt, C.; Lewis, Simon; Upson, E. (Early Childhood Australia Inc., 2011)
Children have immense curiosity, a thirst for knowledge and a questioning attitude. They are innate scientists. The challenge for early childhood educators is to fuel this curiosity through the provision of appropriate learning experiences and an engaging environment within early learning centres. This paper presents a detailed case study of how a pre-service teacher implemented forensic science as a form of scientific inquiry, in a preschool classroom for four-year-old children. Using the theme of 'We’re going on a (forensic) bear hunt!', a series of integrated and engaging experiences was delivered that allowed the children to solve the class mystery of who left behind the (bear) footprints. This paper describes the concept, process and skills of scientific inquiry, outlines the basic principle of forensic science, provides a detailed description of the children’s learning experiences, and interprets these experiences in relation to developing children’s scientific inquiry skills: exploring and predicting, observing and recording, using equipment, using observation as evidence, and representing and communicating. It also illustrates how young children can readily engage in inquiry-based learning; educators, however, must provide the opportunities and support to stimulate this learning. In summary, the paper argues that a complex topic such as forensic science can be successfully implemented with young children, highlighting the competence of these children.